"Phonetic Criticism of Contemporary Poetry: Between Phonological Standards and the Aesthetics of Literary Criticism — An Applied Study on the Poem ‘The Dance of the Mourner’ by Ibrahim Qar’ali." - .belhout, djaloul; bouras, slimane. (El Omda in Linguistics and Discourse Analysis, 2026)
This article focuses on the phonetic criticism of poetry as a critical field that combines traditional linguistic authenticity with modern linguistic data, oscillating between the standard general description of Arabic phonology and the aesthetics of literary criticism open to different styles and contexts. The article aims to establish this field by tracing its roots in the critical heritage and Arabic rhetoric, and exploring its contemporary references derived from modern linguistics, linguistic theories, and critical approaches (formalism and structuralism), in an attempt to answer a central question: How can we construct a comprehensive phonetic critical approach to contemporary Arabic poetry that is capable of analyzing its phonetic structure with its various components and phenomena, based on linking it to the meaning of the text and its various contexts? To clarify this phonetic critical approach, the article presents an applied study of the poem “Raqsat al-Mabka” (The Dance of the Weeping) by the contemporary Algerian poet Ibrahim Qaraali, revealing the role of the phonetic component in shaping meaning, uncovering the semantic structure of the text, and constructing poetic aesthetics.